From Image to Voice: Mira Rosenthal Translates Tomasz Róż ycki - Gorczyńska, Małgorzata (Porównania, 2020)
“From image to voice” is a metaphor of the artistic biography of Mira Rosenthal, the translator of two poetic books by Tomasz Różycki: The Forgotten Keys (2007) and Colonies (2013). Through an analysis of translations and self-commentaries by Rosenthal, the author of the article also indicates the possibility of completing the traditional conception of “implied author’s/ translator’s image” with the concept of “voice”, taking into account non-semantic aspects of a translated text, especially those connected with its sonic structure (the inspiration for such an approach may be found in H. U. Gumbrecht’s works). “Voice” is understood as something more than just a textual representation, an image or a semantic figure of the extratextual creator – it is a material, somatic presence of the translator in the poem.